Architecture for the Secret-Key BC3 Cryptography Algorithm - Arif Sasongko; Hidayat Hidayat; Yusuf Kurniawan; Sarwono Sutikno (LPPM ITB, 2011)
Cryptography is a very important aspect in data security. The focus of research in this field is shifting from merely security aspect to consider as well the implementation aspect. This paper aims to introduce BC3 algorithm with focus on its hardware implementation. It proposes an architecture for the hardware implementation for this algorithm. BC3 algorithm is a secret-key cryptography algorithm developed with two considerations: robustness and implementation efficiency. This algorithm has been implemented on software and has good performance compared to AES algorithm. BC3 is improvement of BC2 and AE cryptographic algorithm and it is expected to have the same level of robustness and to gain competitive advantages in the implementation aspect. The development of the architecture gives much attention on (1) resource sharing and (2) having single clock for each round. It exploits regularity of the algorithm. This architecture is then implemented on an FPGA. This implementation is three times smaller area than AES, but about five times faster. Furthermore, this BC3 hardware implementation has better performance compared to BC3 software both in key expansion stage and randomizing stage. For the future, the security of this implementation must be reviewed especially against side channel attack.